Australian employee perceptions of an organizational-level intervention to reduce sitting. - Brakenridge, C.; Healy, Genevieve; Hadgraft, N.; Young, D.; Fjeldsoe, B. (Oxford University Press, 2017)
Stand Up Lendlease-a cluster-randomized trial targeting reductions in sitting time in Australian office workers (n?=?153, 18 manager-led teams, 1 organization)-effectively reduced sitting time during work hours and across the day after 12?months. The trial included two arms: organizational-support strategies (e.g. manager support, emails) with or without an activity tracker. The current study aimed to examine participant perceptions of the intervention, and perceived barriers and facilitators for reducing sitting time. Telephone interviews (n?=?50 participants; conducted at 6-10?months) and three focus groups (n?=?21 participants; conducted at 16?months) evaluated the intervention with qualitative data analysed thematically. Several consistent themes emerged across both short and long-term time points and intervention groups. Support and role modelling of desired behaviours from important organization personnel and receiving feedback on sitting levels were key drivers of change. Improvements in awareness about sitting, and workplace culture changes supporting active work practices were positive impacts of the intervention, but some participants also reported that initial cultural effects had dissipated and the intervention needed 'reinvigoration'. Participants desired additional 'tools' to maintain sitting less and being active, such as sit-stand desks, standing meeting tables and activity trackers. In summary, the intervention raised awareness and initiated cultural changes towards active work practices, however, additional support may be required to maintain changes in organizational culture long term. Practical tools to support sitting changes, organizational and management support and role modelling, as well as ongoing 'reinvigoration' are key strategies for short and long-term intervention success in office workplaces.